Developing virtual museums towards the smart museum: a theoretical study - Marwa Abdelmajid (Cybrarians Journal)
The study focuses on the latest innovations in virtual applications and virtual reality devices for presenting museum information by reviewing the successive technological developments that have influenced virtual museums, leading to the smart museum. It emphasizes modern technologies and devices that will be associated with the future of the smart museum, particularly communications, artificial intelligence, the metaverse, the Internet of Nothing, and the integration of virtual technologies. The study also highlights libraries that have paid attention to virtual museums, among others, to emphasize the importance of museum information through the virtual content of museums in libraries.